Poetry a writers' guide and anthology - Huey, Amorak; Kaneko, W. Todd (London, UK Bloomsbury Academic, 2018)
"A practical guide to the art and craft of writing poetry including an anthology of contemporary poetry."
Includes bibliographical references and index.
Keywords: Poetry -- Authorship; Poetry; Poetry -- Collections